Ethnoeconomics of Plants as Traditional Medicine (Ethnomedicine) and Food (Ethnoculinary) of the Bastem Indigenous Community in Luwu Regency - Syamsuri Syamsuri; Hasria Alang; Muh. Sri Yusal; Hastuti Hastuti; Adriani Adriani (Jurnal Penelitian Pendidikan IPA, 2023)
Ethnoeconomics is the study of the economic value or use of biological resources by an ethnic group and becomes wisdom. The aim of the research is to inventory the types of plants used as traditional medicine and food by the Bastem indigenous people. The methods used in the research were observation, interviews, focus group discussions (FGD), and literature study, while the sample collection technique used purpose sampling. This type of exploratory research uses a PRR (Participatory Rural Appraisal) approach. The sample criteria used were community leaders and traditional healers. The research data, which is respondents' emic data, is presented in tabular form, then analyzed descriptively and compared with scientific data based on Google Scholar, Sinta, and Research Gate sources. The results of the research show that the types of plants with the economic value used by the Bastem indigenous people as traditional medicine (ethnomedicine) are bangle, galangal, aromatic ginger, white turmeric, coffee leaves, avocado leaves, castor leaves, banana shoots, cat's whiskers, bitter gourd, guava leaves, papaya leaves, lemongrass and ciplukan, while the plants used as food by indigenous communities (ethnoculinary) are grouped into staple foods, vegetables and side dishes, traditional cakes and my day's food. Staple foods include sokko, limestone, corn porridge, sweet potato rice, banana rice and banana sokko. Vegetables and side dishes include green vegetables, burak, and nasu kadundung. Traditional cakes include putu pesse, tori cake, and baruasa. My daily food includes baurasa, gogos, and tumbu'.